2017
DOI: 10.1007/s00018-017-2571-4
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptors in neural stem/progenitor cell homeostasis

Abstract: In the central nervous system, embryonic and adult neural stem/progenitor cells (NSCs) generate the enormous variety and huge numbers of neuronal and glial cells that provide structural and functional support in the brain and spinal cord. Over the last decades, nuclear receptors and their natural ligands have emerged as critical regulators of NSC homeostasis during embryonic development and adult life. Furthermore, substantial progress has been achieved towards elucidating the molecular mechanisms of nuclear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 347 publications
0
16
0
1
Order By: Relevance
“…We observed upregulation of Ascl1, Nr2f1, Crabp2, and Nr6a1 genes (Appendix Fig S1B) in slow/slow NPCs and AGGs. Their overexpression has been previously shown to suppress proliferation of progenitor cells, induce neurogenesis and neuronal maturation (Chanda et al, 2014;Gkikas et al, 2017), and could explain the premature differentiation observed in slow/slow NSCs. In parallel, we observed that the EGF receptor (EGFR) was twofold downregulated in slow/slow NPCs (Table EV2).…”
Section: Role Of Transcriptional Elongation During Neural Differentiamentioning
confidence: 98%
“…We observed upregulation of Ascl1, Nr2f1, Crabp2, and Nr6a1 genes (Appendix Fig S1B) in slow/slow NPCs and AGGs. Their overexpression has been previously shown to suppress proliferation of progenitor cells, induce neurogenesis and neuronal maturation (Chanda et al, 2014;Gkikas et al, 2017), and could explain the premature differentiation observed in slow/slow NSCs. In parallel, we observed that the EGF receptor (EGFR) was twofold downregulated in slow/slow NPCs (Table EV2).…”
Section: Role Of Transcriptional Elongation During Neural Differentiamentioning
confidence: 98%
“…Yet, GR activation during brain development inhibits the migration of post-mitotic neurons in rodents and decreases proliferation and cell survival in both rodent and human neuronal stem cells. In humans, high doses of a GR agonist during pregnancy leads to severe pathologies in children such as cognitive and motor disorders [34].…”
Section: Pathways Linking Ed To Dntmentioning
confidence: 99%
“…Estrogen receptors (ERs) are part of the family of NR3A nuclear receptors and also known as steroid hormone receptors. The estrogen receptor subtypes ER alpha (NR3A1) and ER beta (NR3A2) are expressed in the nucleus, cytoplasm and membrane [ 14 ]. It has been shown that the activation of estrogen receptors by 17 beta estradiol (E2) regulates the proliferation of embryonic NSCs mediated by overexpression of the cyclin-dependent kinase inhibitor, p21 Cip1 [ 15 ], while promoting the proliferation and differentiation to glial cells of NSC embryonic rat in the absence of mitogens Epidermal growth factor (EGF), Fibroblast growth factor-2 (FGF-2) or differentiation factors [ 16 ].…”
Section: Intrinsic Factorsmentioning
confidence: 99%